ANALISIS KELAYAKAN USAHA TANAMAN HIAS DI KOTA PALU - Sulmi Sulmi; Made Antara; Sulaeman Miru (Universitas Tadulako, 2015)
This research aims to determine the feasibility of decor plant entrepreneuer in Palu City.Data was collected through interview and observation. Financial feasibility was determined usingnet present value(NPV), internalrate of return (IRR), payback back period (PBP), Net B/C, and sensitivity analysis. The results showed that NPV analysis indicates that the utilization of money value in the future is positive (IDR 1,054,015.10). IRR analysis performed ahigher value compared to assumed interest rate of 14% per year. The decor plant entrepreneuer in Palu City is capable to pay back the cost of investment which is shown by the value ofPBP of 1 year 10 months. The value of B/C is higher than one (IDR 1.94) suggesting that the décor plants business in Palu City is feasible based on thefinancial aspects. Key words ; Business Feasibility of Decor Plants